The Impact of Feminism on Sociology - Sylvia Walby
The paper investigates the impact of feminism on British sociology over the last 60 years. It focuses on changes in the intellectual content of the discipline, including epistemology, methodology, theory, concepts and the fields of economy, polity, violence and civil society. It situates these changes in the context of changes in gendered organisation of sociology, the rise of women's/gender studies, the ecology of social sciences and societal changes, especially the transformation of the gender regime from domestic to public and the neoliberal turn. It concludes that feminism has had a major impact on sociology, but that the process through which this has taken place is highly mediated through organisational, disciplinary and social processes.[No keywords]